دور مواقع التواصل الاجتماعي في تعزيز التعايش السلمي وترسيخ قيم المواطنة لدى الجمهور العراقي: دراسة ميدانية - عبدالستار حميد جديع (PROSPECTIVE RESEARCHES, 2023)
The study aims at defining the role social media play in the field of enhancing peaceful living and establishing the values of citizenship among Iraqi sects that still oppose concepts of partition، class and ethnic conflict after the occupation of Iraq in 2003 and the results of terrorists’ ideologies led to shake the values system of the Iraqi citizen that is related to be longing and defending the country. This study concentrates on the province of Anbar for it had been targeted and occupied by Isis terrorist gangs in 2014 that resulted in displacing people and spreading terrorist thoughts. This research depends on survey and uses questionnaire to collect data relevant to the research. It takes a sample of (250) people randomly selected from Al- Ta'meem Quarter in Ramadi District. This Quaeter is selected for it is a mixture of different Iraqi Sects and different tribes in order to know the similarities and differences of the effects of social Media in enhancing Peaceful living and establishing Values of citizenship among representative of these sects after the Isis terrorism period. This research finds out 1. Most subjects believe that images shown in social media are positive to percentage of 72.8%. 2. Most subjects think that Iraqi Republic and its establishments did not make use of social media for the benefit of enhancing peaceful living and establishing values of citizenship through these websites to a percentage. 3. It is obvious that the subject’s answers see the social media has a great affect in enhancing peaceful living and establishing values of citizenship to a peaceful of 68.4%.